Keterangan Ahli Warga Negara Asing dalam Peradilan Pidana di Indonesia - Vika Ayu Wandari (University of Jember, 2018)
Proof plays an important role in the process of adjudication in the trial process. In the criminal process, proof requires the attendance of an expert, particularly when it deals with an expert from abroad to provide statements in the courts. This paper aims to show the importance of evidences in the Indonesian criminal law procedure in which the statement to be delivered by an expert from abroad. It will discuss the importance of expert’s statement from foreign citizen to help judges in the criminal justice system of Indonesia. To judges, the statement of an expert has a power characterised as free and non-binding evidence by which the judgement fully depends upon judges’ conviction. While a foreign citizen arrives in Indonesia designated as an expert to provide witness in the trial process in which he/she does not hold visa, judges cannot dispute his/her absence of visa , but they are only given a power to consider the statement of such expert. With regard to visa, it is not the responsible of judges or the court, but the Immigration Bureau. Keywords: Proof, Evidence, Statement of Expert